2021
DOI: 10.24925/turjaf.v9i6.968-974.3758
|View full text |Cite
|
Sign up to set email alerts
|

Review on Production of Single-Cell Protein from Food Wastes

Abstract: The roles of protein in bodybuilding and the regulation of biological processes are important in sustaining life. A large amount of protein is required by both humans and animals and this cannot be supplied by only conventional sources. This is because of the rapid increase in world population. The present sources of protein will not meet global protein demand in years to come. Scientists explore the production of single-cell protein (SCP), as an alternative source of protein, through the utilization of wastes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…SCP can be a good substitute for expensive conventional protein sources like soy meal as well as protein-based ingredients included in the formulation of animal feed such as fishmeal and meat meal [78]. Research has demonstrated single-cell protein production from waste derived from oranges, lemon, corn stover [76], pineapple, mango, banana, apple, cashew apple, jackfruit, cacao, pomegranate [79], cheese, coffee [80], and fish [75]. On the other hand, regulatory obstacles and uncertainties about the safety of the products in relation to harmful or antinutritional substances still exist.…”
Section: Bioconversionmentioning
confidence: 99%
“…SCP can be a good substitute for expensive conventional protein sources like soy meal as well as protein-based ingredients included in the formulation of animal feed such as fishmeal and meat meal [78]. Research has demonstrated single-cell protein production from waste derived from oranges, lemon, corn stover [76], pineapple, mango, banana, apple, cashew apple, jackfruit, cacao, pomegranate [79], cheese, coffee [80], and fish [75]. On the other hand, regulatory obstacles and uncertainties about the safety of the products in relation to harmful or antinutritional substances still exist.…”
Section: Bioconversionmentioning
confidence: 99%
“…5 Single-cell protein (SCP) is the microbial protein produced using food, industrial and agricultural waste, opening new vistas to meet the growing demands of protein. [6][7][8][9] All of these feedstocks are relatively cheaper and could be a potential source of protein production in the future. The concept of microorganism-based protein has been explored for centuries.…”
Section: Introductionmentioning
confidence: 99%